2020
DOI: 10.1016/j.ijrobp.2020.07.2215
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability Evaluation of Sintilimab in Combination with Low Dose Radiation and SBRT in Treatment Naive Stage IV PD-L1 Positive NSCLC Patients

Abstract: The number of pulmonary nodules identified incidentally or through lung cancer screening programs has dramatically increased. The role of radiation therapy (RT) in this patient population is not defined. Our institution established a multidisciplinary Pulmonary Nodule and Lung Cancer Screening Clinic (PNLCSC) to optimize the management of these patients. In this study, we describe the role of radiation oncologists in the multidisciplinary evaluation and management of incidental and screening-identified pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…No grade 3 or above treatment-related toxicity was observed, and the incidence of grade 2 or above radiation-related pneumonitis and immune-related pneumonitis was <10% in a prospective clinical trial. 149 No LDRT-related adverse effect (AE) was reported in another small-sample phase I clinical trial. 87 Data from a phase II clinical study showed no significant difference in the incidence of dose-limiting toxicity between the combined LDRT and non-combined LDRT group.…”
Section: Toxicity Of Ldrtmentioning
confidence: 99%
See 1 more Smart Citation
“…No grade 3 or above treatment-related toxicity was observed, and the incidence of grade 2 or above radiation-related pneumonitis and immune-related pneumonitis was <10% in a prospective clinical trial. 149 No LDRT-related adverse effect (AE) was reported in another small-sample phase I clinical trial. 87 Data from a phase II clinical study showed no significant difference in the incidence of dose-limiting toxicity between the combined LDRT and non-combined LDRT group.…”
Section: Toxicity Of Ldrtmentioning
confidence: 99%
“…Another important issue is the frequency of administration. The relatively traditional RT mode adopted one-time RT (once or several fractions in succession), 81,143,149 RT (periodic administration) was believed to rescue the decline of immune cells over time after LDRT. 87,150,151 There are no evidencebased recommendations for the best immunotherapeutic drug combined with LDRT.…”
Section: Current Challenges: Dose Frequency Drugs Sequence and Implem...mentioning
confidence: 99%
“…In the dose escalation phase of a phase I study (NCT03812549), the synergistic anti-tumor effect of LDRT combined with sintilimab following SBRT was explored in 12 stage IV NSCLC patients, with primary endpoints of safety and tolerability [ 53 ]. The combination plan showed no dose-limiting toxicities, with no grade 3 or higher AEs, while the ORR among 10 evaluable patients was 70% [ 53 ].…”
Section: Clinical Trials Of Sintilimabmentioning
confidence: 99%
“…In the dose escalation phase of a phase I study (NCT03812549), the synergistic anti-tumor effect of LDRT combined with sintilimab following SBRT was explored in 12 stage IV NSCLC patients, with primary endpoints of safety and tolerability [ 53 ]. The combination plan showed no dose-limiting toxicities, with no grade 3 or higher AEs, while the ORR among 10 evaluable patients was 70% [ 53 ]. Interestingly, the combination therapy increased the number of T cell clones and TCR diversity, and decreased the PD-1 expression on CD8 + T cells and circulating tumor DNA (ctDNA) in the patients’ peripheral blood samples [ 53 ].…”
Section: Clinical Trials Of Sintilimabmentioning
confidence: 99%
See 1 more Smart Citation